Faktor-Faktor Yang Berhubungan Dengan Kelelahan Kerja Pada Buruh Di Pelabuhan Soekarno Hatta - Tanri Abeng, Tenri Diah; Pratiwi, Adhinda Putri (Pendidikan Jasmani, Kesehatan, dan Rekreasi, 2024)
Fatigue is a physical and mental condition that results in decreased working power and reduced body resistance to work. Based on a survey conducted, it was found that most workers who work at the Soekarno Hatta port complain about the workload they do every day. As for complaints of fatigue, workers feel a heavy feeling in the head, feel sleepy and feel tired throughout the body. The aim of this research is to find out what factors are associated with work fatigue in workers at the Soekarno Hatta port. The type of research used is observational analytics with a cross sectional design. The population in this study was 54 workers and the sample for this research was the total sampling or total population of 54 workers. Respondent data was collected using a questionnaire. Data analysis uses the Chi-Square Test. The results of this study show that there is a relationship between age (p=0.007), gender (p=0.010), and workload (p=0.000) with work fatigue in workers in Soekarno Hatta Harbor. Suggestions that can be given are that it is hoped that companies will pay more attention to the welfare of workers, and it is hoped that companies will be able to overcome work fatigue for workers. It is also recommended to replace human labor with machines if it is possible to reduce the workload on workers.